2016
DOI: 10.1002/poc.3664
|View full text |Cite
|
Sign up to set email alerts
|

Stability of merocyanine-type photoacids in aqueous solutions

Abstract: Over the past years, protonated merocyanines (MEHs) have been used as photoacids to control various chemical, material, and biological processes using visible light. For the applications under aqueous conditions, stability of this type of photoacid has been a concern. While hydrolysis of merocyanines is well known, this work showed that deprotonation of MEH to form merocyanine is not necessary for the hydrolysis of MEH. The decomposition products were identified by ultraviolet‐visible spectroscopy and liquid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 17 publications
1
66
0
Order By: Relevance
“…35,96,99,[112][113][114][115][116][117][118][119][120][121] Although aqueous environments are known to accelerate hydrolysis of especially the merocyanine form (within hours), hydrolysis is generally slower at lower pH. 122 Notably, incorporating a pyridinium in the chromene moiety of similar water-soluble spiropyrans greatly increases aqueous thermal stability to weeks by favouring the more stable ring-closed spiropyran form, while still operating as a photoacid. 109,123,124 The application of spiropyrans, typically but not only the sulfonate form, as a photoacid requires that the apparent pK a of the acid to be deprotonated is greater than that of the ringclosed spiropyran, but less than that of the ring-opened E-form (Scheme 16).…”
Section: Scheme 15mentioning
confidence: 99%
“…35,96,99,[112][113][114][115][116][117][118][119][120][121] Although aqueous environments are known to accelerate hydrolysis of especially the merocyanine form (within hours), hydrolysis is generally slower at lower pH. 122 Notably, incorporating a pyridinium in the chromene moiety of similar water-soluble spiropyrans greatly increases aqueous thermal stability to weeks by favouring the more stable ring-closed spiropyran form, while still operating as a photoacid. 109,123,124 The application of spiropyrans, typically but not only the sulfonate form, as a photoacid requires that the apparent pK a of the acid to be deprotonated is greater than that of the ringclosed spiropyran, but less than that of the ring-opened E-form (Scheme 16).…”
Section: Scheme 15mentioning
confidence: 99%
“…The ground state Compound 1 was synthesized by condensation of the corresponding Fisher's base with salicylaldehyde, and fully characterized by high-resolution mass spectrometry (HR-MS), 1 H and 13 C NMR spectroscopy, as well as X-ray analysis (see ESI † for more details). Our investigations started from a simple observation: aqueous solutions of compound 1, under dark conditions and at known concentration, exhibited pH values diverging substantially from those expected considering previously reported 5,6,21 pK a estimates. Initially, we ascribed this outcome to possible differences in (i) temperature and (ii) ionic strength of the sample, as well as (iii) equilibration time before data collection, which are all common parameters to which direct pH readings are sensitive to.…”
Section: Resultsmentioning
confidence: 86%
“…Spirooxazine derivatives exhibit a better fatigue resistance than spiropyran derivatives [64][65][66][67]. One of the ways to investigate the fatigue resistance of spirooxazine derivatives is to monitor the change in relative absorption intensity at λ max in every photochromic cycle [68,69]. As shown in Figure 10, the photochromic cycles were conducted ten times, and a maximum decrease of 0.85% in relative absorption intensity of the colored form of NC-g-AISO membrane indicated that NC-g-AISO membrane has good reversible photochromic behavior.…”
Section: Discussionmentioning
confidence: 99%